Serum TNF-α Level Is Associated with Disease Severity in Adult Patients with Immunoglobulin A Vasculitis Nephritis. (25th November 2020) - Wu, Haiting; Wen, Yubing; Yue, Cai; Li, Xuemei; Gao, Ruitong
Abstract : Background . Tumor necrosis factor- α (TNF- α ) is a proinflammatory factor involved in the pathogenesis of immunoglobulin A vasculitis (IgAV). The association between serum TNF- α and disease severity in adult patients with IgAV nephritis (IgAV-N) has been inadequately evaluated. Methods . Serum TNF- α was measured by chemiluminescence immunoassay in 53 renal biopsy-proved IgAV-N patients, 53 healthy controls, and 53 IgA nephropathy (IgAN) patients. The correlations of clinicopathologic parameters of IgAV-N patients with serum TNF- α were analyzed. Results . In this cross-sectional study, the median age of IgAV-N patients was 29 (25-37) years, and 67.9% were female. Serum TNF- α was significantly higher in the IgAV-N group than in the healthy group [7.4 (5.7-9.4) pg/mL vs. 5.9 (5.0, 7.1) pg/mL, P = 0.001 ], but comparable with sex, age, and estimated glomerular filtration rate (eGFR) grade-matched IgAN patients. Serum creatinine (P = 0.006 ) and serum cystatin C (P = 0.001 ) were positively correlated with serum TNF- α level, while albumin (P = 0.014 ) and eGFR (P = 0.021 ) were negatively correlated with serum TNF- α level. Multivariate linear regression analysis revealed that eGFR (P = 0.007 ) was an independent clinical predictor of serum TNF- α . Patients with higher pathological classification grade also had higher serum TNF- α . Conclusions . Serum TNF- α is associated with renal function and the pathological classification of adult patients with IgAV-N. TNF- α is a potential biomarker for the assessment of IgAV-N severity.